Modelling technical compromises in electronics manufacturing with BPMN+TD – an industrial use case. Issue 1 (2021) - Dong, Quang Huan; Vogel-Heuser, Birgit
Abstract: Relocating manufacturing plants is a phenomenon nowadays due to increasing changes in markets, materials, and labour cost. Under business pressure, while transferring the manufacturing systems, some technical compromises might be taken to start the production as soon as possible. A technical shortcut can provide a short-term benefit but may introduce a long-term negative impact. This work reports an industrial use case at a world-leading electronics manufacturer during its plant relocations. The study employs the Business Process Model and Notation (BPMN) to visualize the use case. There, an enlargement of BPMN, namely BPMN+TD, is achieved to assist in modelling TD artifacts.